Outcomes and Laboratory and Clinical Findings of Asthma and Allergic Patients Admitted With Covid-19 in a Spanish University Hospital - García-Menaya, Jesús Miguel; Cordobés-Durán, Concepción; Rangel-Mayoral, Juan Francisco; García-Martín, Elena; Agúndez, José A. G. (Frontiers in Pharmacology, 2020)
Individual susceptibility and clinical outcome of Covid-19 are variable and mortality is also very variable across countries, being particularly high in Spain. Comorbidities might increase the risk for less favourable outcomes, but it has been reported that patients with antecedents of asthma or allergic diseases were under-represented among hospitalized Covid-19 patients. Aiming to compare the clinical evolution of patients with antecedents of asthma or allergic diseases and patients without these antecedents, we analyzed a series of 113 consecutive patients with Covid-19 in a regional hospital in Spain. We collected and analyzed the putative effect of the 16 most common co-morbidities, previous treatment with 33 drug classes, symptoms, radiological, and laboratory findings at admission and drug therapy after admission. Predictors of long hospital stays were older age (P = 0.002), low oxygen saturation (P = 0.001) and bilateral radiological findings at admission (P = 0.023). Predictors of Intensive Care Unit (ICU) admission were the previous use of calcium-channel blockers (P = 0.005), proton pump inhibitors (P = 0.017), low oxygen saturation (P = 0.002), high leukocyte count (P = 0.011), and high D-dimer values (P = 0.005). Predictors of mortality were older age (P = 0.001), antecedents of cerebrovascular disorders (P = 0.034), previous use of oral anticoagulants (P = 0.009) or selective serotonin reuptake inhibitors (P = 0.003), and increased levels of interleukin-6 (P = 0.001). Patients with antecedents of allergic diseases were about ten years younger (P = 0.003) and had fewer comorbidities (P = 0.026) than the rest of the patients. In conclusion, antecedents of allergic diseases might influence hospitalization risk in relatively young patients.